Population structure, relative growth and morphological sexual maturity of the snapping shrimp Alpheus brasileiro Anker, 2012 (Caridea: Alpheidae) from the south-eastern coast of Brazil - Pescinelli, Régis Augusto [UNESP]; Almeida, Alexandre Oliveira; Costa, Rogério Caetano [UNESP] (Taylor & Francis, 2018)
The present study investigated the population structure of the snapping shrimp Alpheus brasileiro. We tested the hypotheses that the sex ratio of the population differs from the expected 1:1 and that the growth pattern differs between adults and juveniles and between sexes. Reproductive period, juvenile recruitment and morphological sexual maturity were estimated. Samples were collected in two periods. The first sampling occurred bimonthly from March 2013 to January 2014. The second sampling occurred monthly from April 2015 to March 2016. The population structure was determined based on the size-frequency distribution of different demographic categories. To analyse the relative growth, we measured the second pleuron length, major cheliped propodus length, major cheliped propodus width, major cheliped propodus height, appendix interna length, appendix masculina length. The results showed that the sex ratio did not differ from 1:1 (male:female). Reproduction and juvenile recruitment were continuous throughout the study period. The analysis of relative growth confirmed the hypothesis that males and females, and juveniles and adults, have different growth patterns, indicating distinct strategies of energy allocation. The estimated carapace length at the onset of morphological sexual maturity was 4.9 mm in males and 4.7 mm in females. The results obtained in this study are probably related to the monogamous social behaviour of A. brasileiro. Monogamy can influence demographic parameters such as sex ratio and the size at which males and females reach morphological sexual maturity.
Keywords: allometry; Audrey J. Geffen; energy allocation; Population structure; sex ratio; sexual maturity